FEATURES OF HEART LESION IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS (LITERATURE REVIEW) - V. Dubovyk; V.E. Kondratiuk (Bogomolets National Medical University, 2018)
Summary. An analysis of national and foreign scientific literature about the features of heart damage in systemic lupus erythematosus (SLE) is carried out. This topic is very relevant, because according to different authors, the frequency of cardiovascular system (CVS) damage in SLE ranges from 52 to 89%. Mortality because of SLE is three times higher than in the population, while among its causes, CVS ranks third after infections and renal failure. The results of numerous studies about the features of the clinical picture, diagnosis and treatment of SLE patients with primary lesions of the heart are presented and analyzed. Particular attention is paid to lupus myocarditis (LM), endocarditis Libman-Sacks, as well as rhythm and conduction disturbances. LM often makes its debut at early stage of SLE and in most cases is not clinically manifested. That is why LM is difficult to diagnose. LM can lead to arrhythmias, conduction disturbances, dilated cardiomyopathy (DCM), heart failure (HF) and even sudden death. The myocardium is involved in the pathological process according to autopsy in 40-80% of cases, but cardiovascular disorders are absent only in 7,5% of patients. Echocardiography (EchoCG), speckle-tracking EchoCG, MRI of the heart are necessary methods for the diagnosis of active or transferred LM. Early aggressive immunosuppressive therapy significantly improves the prognosis. The detection rate of pericarditis in SLE is 25,6%. It was found in 62,1% of cases according to autopsy results. Pericarditis is usually combined with endocarditis or endomocarditis. The morphological basis of heart defects that are formed in SLE is non-bacterial endocarditis of Libman-Sacks. The frequency of endocarditis is 73,3%. The course of endocarditis is predominantly benign and does not cause significant hemodynamic disturbances. The frequency of rhythm disturbance remains quite high in all age groups of patients with SLE. It's diagnosis is difficult due to the asymptomatic course and frequent joining of concomitant cardiovascular pathology.